Pengembangan Media Interaktif Augmented Reality (AR) Pada Topik Mengenal Organ Pernapasan Manusia di Kelas V Sekolah Dasar - Umam, Azmil; Tanjung Sari, Tita; Puniman, Ach.; Daniel Wahyudi, Eko (IJPSE Indonesian Journal of Primary Science Education, 2024)
The rapid development of technology provides various changes in human life factors. The world of education can take advantage of technological developments to encourage quality learning, one of which is by utilizing technology as one of the media to maximize the learning process. this study aims to: (1) To find out how the Development of Interactive Media Based on Augmented Reality (AR) on the Topic of Knowing Human Respiratory Organs in Class V Elementary School, (2) To find out how the teacher's response and student response to Interactive Learning Media Based on Augmented Reality (AR) on the Topic of Knowing Human Respiratory Organs in Class V Elementary School. This research is a development research using the 4-D development model from Thiagarajan which consists of design, define, develop, dessiminate. the results of the percentage of product feasibility from the validator are 90% material validation while 92.5% media validation with the category "Very Good". Teacher responses obtained through questionnaires resulted in a response assessment with a percentage of 100% in the "Very Good" category. Student response in the limited trial of 8 student subjects resulted in a response percentage of 88% and in the free trial of 10 student subjects resulted in a response percentage of 96% in the "Very Good" category.